2017
DOI: 10.1007/s00404-017-4373-1
|View full text |Cite
|
Sign up to set email alerts
|

What do patients want to know about contraception and which method would they prefer?

Abstract: The small number of women who use long-term contraception is in clear contrast to the fact that many women want to have a very safe but also behavior-independent method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 10 publications
1
34
0
14
Order By: Relevance
“…The TANCO study found that nearly half of German women using a combined (n ¼ 10,461) or progestogen-only (n ¼ 922) contraceptive pill reported missing at least one pill during the previous 3 months (48% combined pill, 46% progestogen-only pill). Of those aged 20-29 years, the overall figure was 47% [12]. In an interview-based study of 1978 US women at risk of unintended pregnancy, Frost et al [10] found that 45% of 18to 24-year-old and 34.5% of 25-to 44-year-old oral contraceptive pill users reported missing at least one pill during the previous 3 months.…”
Section: Findings and Interpretation And Similarities And Differencementioning
confidence: 99%
See 4 more Smart Citations
“…The TANCO study found that nearly half of German women using a combined (n ¼ 10,461) or progestogen-only (n ¼ 922) contraceptive pill reported missing at least one pill during the previous 3 months (48% combined pill, 46% progestogen-only pill). Of those aged 20-29 years, the overall figure was 47% [12]. In an interview-based study of 1978 US women at risk of unintended pregnancy, Frost et al [10] found that 45% of 18to 24-year-old and 34.5% of 25-to 44-year-old oral contraceptive pill users reported missing at least one pill during the previous 3 months.…”
Section: Findings and Interpretation And Similarities And Differencementioning
confidence: 99%
“…Obstetrician-gynaecologists, general practitioners and nurses should be aware of typical adherence to daily contraceptive pill regimens among millennial womenwhich have been shown to be overestimated by health care providers (HCPs) [12] and ensure each contraceptive counselling session includes a discussion around potential barriers to adherence. Unless prompted, young women may be unlikely to discuss such areas, relying on their HCP their key influencerto guide them.…”
Section: Relevance Of the Findings: Implications For Clinicians And Pmentioning
confidence: 99%
See 3 more Smart Citations